1999
DOI: 10.1074/jbc.274.22.15615
|View full text |Cite
|
Sign up to set email alerts
|

A Pathway for Conformational Diversity in Proteins Mediated by Intramolecular Chaperones

Abstract: Conformational diversity within unique amino acid sequences is observed in diseases like scrapie and Alzheimer's disease. The molecular basis of such diversity is unknown. Similar phenomena occur in subtilisin, a serine protease homologous with eukaryotic pro-hormone convertases. The subtilisin propeptide functions as an intramolecular chaperone (IMC) that imparts steric information during folding but is not required for enzymatic activity. Point mutations within IMCs alter folding, resulting in structural con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 45 publications
5
59
0
1
Order By: Relevance
“…The predicted structure in boldface represents predictions that do not match with the secondary structure obtained from the crystallized complex of ProWT⅐subtilisin. Motifs N1 and N2 represent the conserved domains within the subtilase family (18). Asterisks denote residues that constitute the hydrophobic core within the propeptide.…”
Section: Fig 1 Design Criteria and Computational Characterization Omentioning
confidence: 99%
See 1 more Smart Citation
“…The predicted structure in boldface represents predictions that do not match with the secondary structure obtained from the crystallized complex of ProWT⅐subtilisin. Motifs N1 and N2 represent the conserved domains within the subtilase family (18). Asterisks denote residues that constitute the hydrophobic core within the propeptide.…”
Section: Fig 1 Design Criteria and Computational Characterization Omentioning
confidence: 99%
“…Because propeptides perform functions different from the catalytic domains, they may be subjected to different mutational frequencies because of different functional constraints (14 -16). However, given that they impart structural information to their catalytic domains (17)(18)(19), propeptides within one family could adopt similar structural scaffolds despite digressions in their polypeptide sequences. This makes propeptides attractive models for protein redesign and for understanding the relation between sequence and structure.…”
mentioning
confidence: 99%
“…A prosequence of subtilisins has been shown to function not only as an intramolecular chaperone but also as a template for molecular imprinting that facilitates correct folding of the catalytic domain (29,30). This prosequence should be removed from the catalytic domain by autoprocessing or by another protease upon completion of the protein folding (31).…”
Section: Vol 67 2001mentioning
confidence: 99%
“…16,17) In a study of serine protease subtilisins and their propeptides, the functions of subtilisin propeptides as intramolecular chaperons and inhibitors were identified, [18][19][20] and the structure of the subtilisinpropeptide complex was also determined. 20) Structural analysis indicated that the C-terminal strand of the propeptide binds to the subtilisin substrate-binding cleft.…”
Section: Discussionmentioning
confidence: 99%